Implementasi Algoritma BCRYPT pada Sistem Informasi Pengaduan Berbasis Website untuk Keamanan Kata Sandi Pengguna - Fatihul Barri Almahmudi; Rosidin Rosidin; Dicky Andika Sulaeman; Sukarsa Sukarsa (LPPM UNU CIREBON, 2025)
The Nahdlatul Ulama Branch Representative Council (MWCNU) of Tanjung District plays a crucial role in providing religious and social services. However, the manual management of public complaints presents various problems, such as delays in handling, lack of documentation, and an unstructured complaint process. This study aims to design and build a website-based complaint information system for MWCNU Tanjung, in order to improve efficiency, transparency, and accountability in complaint management. This system is designed using an information technology approach that supports digital transformation in public complaint management. The method used in this study is a website-based system development method with an agile approach, which involves user needs analysis, system design, implementation, and testing. The result of this study is a website-based information system that can expedite the submission of public complaints, provide better documentation, and enable administrators to follow up on complaints in a more structured and timely manner. This system is expected to improve the quality of MWCNU services in Tanjung District and strengthen the relationship between administrators and the community.